The new tower of Babel: Divergent water quantification in the southwestern United States - Juan Camilo Perdomo Marin (Water Alternatives)
This research contributes to the academic discussions on the politics of water quantification by analysing the factors that generate divergent water figures in the southwestern United States. The controversies surrounding the construction of the Lake Powell Pipeline (LPP) are the case of study as its proponents and opponents use conflicting water data. This analysis associates four kinds of contradictory data related to the LPP with epistemological questions (value, ranking, perspective and delimitation) to explain why having more data does not solve conflicts. Since having adequate data is essential to making informed decisions, this study concludes by calling for a critical review of water figures that considers the logical limits of quantification and the political factors influencing its production and use.